Background complexity can mitigate poor camouflage. Issue 1963 (24th November 2021) - Rowe, Zeke W.; Austin, Daniel J. D.; Chippington, Nicol; Flynn, William; Starkey, Finn; Wightman, Edward J.; Scott-Samuel, Nicholas E.; Cuthill, Innes C.
Abstract : Avoiding detection through camouflage is often key to survival. However, an animal's appearance is not the only factor affecting conspicuousness: background complexity also alters detectability. This has been experimentally demonstrated for both artificially patterned backgrounds in the laboratory and natural backgrounds in the wild, but only for targets that already match the background well. Do habitats of high visual complexity provide concealment to even relatively poorly camouflaged animals? Using artificial prey which differed in their degrees of background matching to tree bark, we were able to determine their survival, under bird predation, with respect to the natural complexity of the background. The latter was quantified using low-level vision metrics of feature congestion (or 'visual clutter') adapted for bird vision. Higher background orientation clutter (edges with varying orientation) reduced the detectability of all but the poorest background-matching camouflaged treatments; higher background luminance clutter (varying achromatic lightness) reduced average mortality for all treatments. Our results suggest that poorer camouflage can be mitigated by more complex backgrounds, with implications for both camouflage evolution and habitat preferences.